Comparison of effects of ketamine, ketamine-dexmedetomidine and ketamine-midazolam on dressing changes of burn patients - Murat Gündüz; Sefika Sakalli; Yasemin Günes; Erol Kesiktas; Dilek Özcengiz; Geylan Isik (Wolters Kluwer Medknow Publications, 2011)
Objective: The aim of this randomized, controlled study was to compare the sedoanalgesic effects of ketamine-dexmedetomidine and ketamine-midazolam on dressing changes of burn patients. Materials and Methods: Following Ethics Committee approval and informed patient consent, 90 ASA physical statuses I and II adult burn patients were included in the study. Patients were randomly divided into three groups. Ten minutes before dressing change, the dexmedetomidine group (group KD) ( n=30) received a continuous infusion of dexmedetomidine at a rate of 1 μg kg-1 , the midazolam group (group KM) ( n=30) received a continuous infusion of midazolam at a rate of 0.05 mg kg-1 and the saline group (group KS) ( n=30) received a continuous infusion of saline intravenously. One minute before dressing change, each patient was administered 1 mg kg-1 ketamine intravenously. Hemodynamic variables, pain and sedation scores, the number of patients requiring additional ketamine, time to dressing change and recovery time were recorded. Results: Systolic blood pressure (SBP) values were significantly lower at, before and after ketamine administration; and 5, 10 and 15 minutes after the procedure in group KD in comparison with the other groups ( P<0.05). There was no significant difference in pain scores among the groups during the study period. Sedation scores were significantly higher in group KD than in groups KM and KS at the end of the first hour ( P<0.05). Time to dressing change and recovery time were similar in all the groups. Conclusion: In burn patients undergoing dressing changes, although both combinations ketamine-dexmedetomidine and ketamine-midazolam offered an effective sedoanalgesia without causing any significant side effect, the former resulted in higher sedation and lower hemodynamic discrepancy.